LAYANAN INFORMASI AKADEMIK MENGGUNAKAN TWITTER DI UNIVERSITAS STIKUBANK (UNISBANK) SEMARANG (Information Technology and Telematics, 2013)
Twitteris asocialmediathat are widely usedtodaybecause ofeasy, fastanddirectprocedureto thedestination, one of the servicesthatare being developedfromtechnologytwitterisaccess toinformation. Withthese developmentsaffectprovidesomefacilitiesthatcan beusedby usersof socialmedia, twitteris atechnology that allows peopletoobtainortransmitinformationwhenever and whereverneeded, in an easy way. Servicesare developedwithprogramming languagesNetbeans, MySQLandtwitter. Development ofAcademic InformationServicescanaddress theproblems associatedwithinformationqualityandclarity ofthe information produced. Keywords :InformationServices, Academic,Twitter.